PENGARUH BOMBARDIR PARTIKEL BERMUATAN TERHADAP SIFAT FISIK PLAT ALUMINIUM DENGAN DIELEKTRIK GAS TETRAFLUOROETANA DALAM MEDAN TINGGI DC NON-HOMOGEN - Ibnu Sabilli; Mochammad Dhofir; Mahfudz Shidiq (Jurnal Mahasiswa TEUB, 2022)
In this study, positive ions were generated from the gas ionization process of tetrafluoroethane (R134a) using a high electric field. The high field is generated at the plate needle electrode array in a gas environment of tetrafluoroethane. The highest field occurs at the needle tip and the ionization process occurs around the needle tip. Each ionization of tetrafluoroethane gas produces one electron and one positive ion. To bombard the plate electrode, positive ions must move from the tip of the needle to the plate electrode. The needle electrode must be supplied with DC voltage of positive polarity while the plate electrode is grounded. The results showed that the positive ion bombardier effect on the physical charactertistic of the aluminum plate depended on the value of the kinetic energy of the ions when it hits the surface of the plate. The longer the free path of the positive ion, the greater the speed and kinetic energy of the ion when it strikes the plate electrode.Keywords – aluminum plate, ion bombardment, positive ion, tetraflouroethane